2021
DOI: 10.1094/phyto-02-21-0054-sc
|View full text |Cite
|
Sign up to set email alerts
|

Spray-Induced Gene Silencing as a Potential Tool to Control Potato Late Blight Disease

Abstract: Phytophthora infestans causes late blight disease on potato and tomato and is currently controlled by resistant cultivars or intensive fungicide spraying. Here, we investigated an alternative means for late blight control by spraying potato leaves with double-stranded RNAs (dsRNA) that target P. infestans genes that are essential for infection. First, we showed that the sporangia of P. infestans expressing Green Fluorescent Protein (GFP) can take up in vitro synthesized dsRNAs homologous to GFP directly from t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…Control leaves were treated with 20 μL 1× PBS buffer instead of a pathogen suspension. This experiment was repeated three times with 5 leaves per treatment and two spots per leaf [ 60 , 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…Control leaves were treated with 20 μL 1× PBS buffer instead of a pathogen suspension. This experiment was repeated three times with 5 leaves per treatment and two spots per leaf [ 60 , 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…Using a similar approach, exogenously applied dsRNAs did not lead to RNAi of target genes in the potato late blight pathogen, Phytophthora infestans (Qiao et al 2021). However, by spray application of dsRNAs onto potato leaves, another study demonstrated that dsRNAs targeting developmentally important pathogen genes coding for guanine-nucleotide binding (G) protein β-subunit (PiGPB1), haustorial membrane protein (PiHMP1), cutinase (PiCUT3), or endo-1,3(4)-βglucanase (PiENDO3) in P. infestans can potentially be used as a tool in controlling potato late blight disease (Kalyandurg et al 2021). These results suggest that the optimal outcomes for SIGS against oomycete pathogens may be strongly influenced by the manner in which the dsRNA is applied.…”
Section: Sigs To Control Fungal and Oomycete Plant Pathogensmentioning
confidence: 99%
“…SIGS of F. graminearum AGO and DCL genes protects barley leaves from F. graminearum infection (Werner et al 2020). Moreover, SIGS has been adopted to compromise Verticillium wilt in tomato (Song and Thomma 2018) and late blight disease in potato (Kalyandurg et al 2021). It is needed to note that the efficiency of SIGS for disease control largely depends on the efficiency of RNA uptake by pathogens and the secondary amplification of siRNA machinery (Qiao et al 2021;Song and Thomma 2018).…”
Section: Srna-based Technologies In Engineering Disease Resistancementioning
confidence: 99%
“…For example, a major hurdle in the practical application of SIGS is the rapid degradation of naked RNAs. To overcome this problem, nanomaterials such as chitosan-complexed single-walled carbon nanotubes (Demirer et al 2019;Kwak et al 2019) and layered double hydroxide (LDH) clay nanosheets (Qiao et al 2021), may be used to deliver and stabilize sRNAs. These new approaches not only facilitate biomolecule transport into plant cells with high efficiency and without toxicity or tissue damage but also protect RNA cargo from nuclease degradation.…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation